Tsunami Mitigation Strategy at Watu Ulo Beach Based on Numerical Modeling Using Delft3D-Flow - Risqi Sofiana; Retno Utami Agung Wiyono; Indra Nurtjahjaningtyas (Kadiri University, 2022)
The coastal area of Watu Ulo Beach in Jember has great resource potential but also the potential for major disasters, such as a tsunami. Tsunamis can cause casualties and destroy buildings. Thus, it is important to assess the possibility of future tsunami disasters. This study aims to simulate a tsunami at Watu Ulo Beach using Delft3D-Flow to analyze the possibility of affected areas. The tsunami modeling is based on two simulations, namely Scenario 1 as model validation using the characteristics of the 1994 Banyuwangi earthquake. Model validation calculation uses the MAPE method <10%. Scenario 2, modeling the southern Java megathrust earthquake, was analyzed to obtain the time and wave height as well as tsunami run-up and inundation, visualizing the area affected by Watu Ulo Beach. The simulation results show that the tsunami wave height at Watu Ulo Beach reached 12.57 m with a travel time of 29 minutes. The run-up elevation was 9.21 m, and the inundation distance was 2.38 km from the Watu Ulo coastline, indicating that the tsunami caused substantial damage. As an area affected by the tsunami, Sumberejo Village has an inundation area of 634.68 ha, and Sabrang Village has an area of 250.03 ha. The temporary evacuation location for Watu Ulo Beach is set at Tanjung Papuma Street via the shortest route of 0.57 km from the assembly point. Based on the results of this study can be used as a reference for determining temporary evacuation routes and locations for tsunami disaster mitigation in coastal areas.